Collaboration of Families and Teachers as a Factor of Encouragement of Social Education - Alifanoviene, Daiva; Radzeviciene, Liuda; Musvicienė, Zydra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Article reveals peculiarities of collaboration between parents and teachers in the education environment and development of collaboration opportunities. Successive impure strategy of research combining quantitative and qualitative methods is presented. Opinion on collaboration attributes of family members and school teachers (N=176) is analyzed according to the semi structured interview data and applying method of Content analysis. Results of quantitative research that was done using questionnaire reveal peculiarities of collaboration in the process of social education highlighting successful and non-successful areas of collaboration discussed as well.